Green and Lean Management - Machado, Carolina; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focusses on the challenges and changes organizational management faces in an era when the need to develop environmentally aware processes meets high levels of competition. It covers the synergetic effects, how re-use, recycling, waste reduction, and other sustainable production strategies can add value, low costs and time of production. Sustainable business behavior is not only an environmental perspective on management, but more and more contains an organizational perspective. Taking into account these issues, green and lean management appears as the way managers can drive their employees to continuously improve the management processes that add value to the organization and costumers. This book provides information on principles, strategies, models, and applications of green and lean management, and at the same time communicates the latest research activity relating to this scientific field world-wide.
Introduction: Challenges Organizational Management Faces -- The Green Side: Methodologies for a more Sustainable Management -- The Lean Side: Strategies for Cost and Production Time Reductions -- Synergetic Effects of Green and Lean Management -- Examples from Industry and Academia.
Keywords: Industrial Management; Energy policy; Energy and state; Production management; Industrial Management; Energy Policy, Economics and Management; Operations Management